The Mixture Of Bio-Oil And Biochar Produced From Slow Pyrolysis Of Oil Palm Wastes For Briquettes Production And Combustion As Solid Fuels - Safana, Aminu Aliyu (2018)
Malaysia generates an enormous amount of agricultural wastes, especially from the oil palm wastes industries. These wastes will continue to bring about the agricultural wastes disposal problem in Malaysia until necessary measures are taken to upgrade their applications. The primary aim of this study is to upgrade the application of these wastes for briquettes formation as a source of heat. In this study, the effect of torrefaction to upgrade higher heating value (HHV) of empty fruit bunches (EFB), mesocarp fibre (MF) and palm kernel shell (PKS) was investigated. The production of durable and qualitative biomass and charcoal briquettes from raw samples and torrefied products (biomass briquettes), and biochar and bio-oil (charcoal briquettes) obtained from pyrolysis were investigated.